Subtype B Human Immunodeficiency Virus (HIV) Type 1 Mutant That Escapes Detection in a Fourth-Generation Immunoassay for HIV Infection - Gaudy, Catherine (American Society for Microbiology, 2004)
We report a case of human immunodeficiency virus (HIV) type 1 infection not detected by a highly sensitive combined antigen-antibody assay. The virus was a subtype B strain harboring a unique sequence within the immunodominant epitope of the transmembrane glycoprotein. Immunochemical analysis indicated that this sequence was probably responsible for the failure to detect HIV antibodies.